(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2021)
Research suggests that academic self-concept influences academic gains. This has important implications for literacy acquisition. Facilitating the development of reader and writer self-concept has been found to support literacy gains. For this reason, it is essential that educators actively work to bolster student self-concept. Best practice recommendations for helping students develop positive reader and writer self-concept include helping students establish reader and writer identity, using the classroom environment to empower readers and writers, and developing supportive teacher-child relationships. The author acknowledges that the relationship between academic achievement and self-concept is reciprocal. As such, quality literacy instruction is needed in addition to attending to the affective factor of self-concept in order for students to be successful readers and writers.